ECONOMIC ASSISTANCE POLICY IN AFRICA: THE RIVALRY BETWEEN CHINA AND JAPAN (Journal of International Studies, 2023)
This paper aims to analyze the China and Japan rivalry on economic assistance policy in Africa using a qualitative method and nationalinterest as the conceptual framework. The land of Africa has abundant reserves of natural resources, such as dense forestry andmineral resources which naturally will attract foreign investors. The first foreign investors in Africa were westerners. Within the grip oftheir iron fists, Africa experienced a bitter history of slavery and colonialization. This rooted problem remains unresolved and causesa significant political atrophy until this day, and has resulted in the incapability of the Africa nations to resolve their own respectiveproblems. Given such a state of affairs, these former colonies in Africa have always been longing for foreign assistance, especiallyafter the post-Cold War Era. Thus, the abandonment of former colonies gave the opportunity for the Eastern powers, such Chinaand Japan to establish a foothold in Africa, namely Japan with its Tokyo International Conference on African Development (TICAD)and China its Belt and Road Initiative (BRI). Through the TICAD, Japan emphasizes the importance of “Africa’s Ownership” in all itsinfrastructure development cooperation initiatives. On the other hand, Chinese assistance can be characterised as indiscriminate, reciprocal, and non-interference in internal affairs. This paper suggests that both China and Japan have their own respective agenda on how to conduct diplomacy in Africa. They even share the same goals vis-a-vis Africa, which are economic and political domination and a keen interest in exploiting the available natural energy resources.